ESTIMATION OF AREAL FREQUENCY AND MEAN TRACE LENGTH OF DISCONTINUITIES OBSERVED IN NON-PLANAR SURFACES - Song J.-J. (My University, 2006)
Mauldon (1998) suggested end-point estimators of areal frequency and mean trace length for a planar sampling window which were recently proved to be unbiased maximum likelihood estimators by Lyman (2003). The present paper is to expand the concept and applicability of the end-point estimators to those for a general non-planar sampling window. The generalized end-point estimators are verified and its applicability for variable discontinuity orientation is checked by Monte Carlo simulation. Standard deviation of estimation error and estimation efficiency of areal frequency and mean trace length are also considered.
Keywords: END-POINT ESTIMATOR; AREAL FREQUENCY; MEAN TRACE LENGTH; NON-PLANAR SAMPLING WINDOW